Investigation of The Effect of Pre-Service Classroom Teachers’ Critical Thinking Disposition on Their Media Literacy - Özkan Çelik; Halil Çokçalişkan; Alper Yorulmaz (Institute of Advanced Engineering and Science, 2018)
It is important to develop a critical perspective in terms of interpreting the messages to be given to the individuals through media and questioning the authenticity and content of these messages. It is therefore necessary to train the individuals called media literate who can critically perceive and evaluate the information conveyed through the media to increase the positive effects of the media and to reduce their negative effects as much as possible. The purpose of the current study is to investigate the effect of the pre-service teachers’ critical thinking disposition on their media literacy. The study employed the relational survey model, one of the quantitative research methods. In order to collect data, a personal information form, the Critical Thinking Disposition Scale, and the Media Literacy Level Determination Scale were used as the data collection tools. As a result of the study, the critical thinking disposition of the pre-service teachers was found to be medium and their media literacy was found to be high. The critical thinking disposition was found to be varying significantly depending on their gender and grade level; their media literacy was found to be varying depending on grade level but not on gender. There is a positive but low relationship between critical thinking disposition and media literacy and critical thinking is a significant predictor of media literacy.